2015
DOI: 10.2340/00015555-2023
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody Levels and Clinical Disease Severity in Patients with Pemphigus: Comparison of Aggregated Anti-desmoglein ELISA Values and Indirect Immunofluorescence Titres

Abstract: Detecting serum-autoantibodies by anti-Desmoglein-1 (anti-Dsg1) and anti-Dsg3 ELISAs as well as indirect immunofluorescence (IIF) are established complementary methods to diagnose pemphigus. Whether autoantibody levels also reflect clinical disease activity is still a matter of debate, as head-to-head comparisons of ELISA values and IIF titres with clinical activity over a longer treatment period are scarce. In our retrospective study, we compared aggregated repetitive intra-patient ELISA values and IIF titres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 44 publications
0
17
1
1
Order By: Relevance
“…Circulating immunoglobulin G (IgG) antibodies against BP180 and BP230, desmoglein 1 and 3 (all Medical Biologicals Laboratories Co. Ltd, Nagoya, Japan) were detected using commercially available ELISA-kits according to the manufacturer's instructions. IIF studies were performed on monkey oesophagus sections as previously described (Inova Diagnostics, CA, USA) (19). Briefly, patient sera were diluted at 1:10 and incubated on monkey oesophagus slides for 30 min at room temperature.…”
Section: Immunological Assaysmentioning
confidence: 99%
“…Circulating immunoglobulin G (IgG) antibodies against BP180 and BP230, desmoglein 1 and 3 (all Medical Biologicals Laboratories Co. Ltd, Nagoya, Japan) were detected using commercially available ELISA-kits according to the manufacturer's instructions. IIF studies were performed on monkey oesophagus sections as previously described (Inova Diagnostics, CA, USA) (19). Briefly, patient sera were diluted at 1:10 and incubated on monkey oesophagus slides for 30 min at room temperature.…”
Section: Immunological Assaysmentioning
confidence: 99%
“…Hazırlanan preparatlar ultraviyole mikroskopu ile incelenir (Şekil 2). Tanıdaki değerinin yanında, bazı çalışmalarda İİF titrelerinin klinik hastalık aktivitesi ile direk ilişkili olduğu, hastalık takibinde ve tedavi yanıtının değerlendirilmesinde kullanılabileceği öne sürülmüşse de son çalışmalar İİF titrelerinin klinik hastalık aktivitesini yansıtmada yetersiz olduğunu desteklemektedir (5). Bizim yaptığımız bir çalışmada ise İİF titreleri pemfigus hasta grubunda klinik aktivite ile uyumlu olsa da prediktif değerinin istatistiksel olarak anlamlı olmadığı saptanmıştır (6).…”
Section: İndirekt İmmünofloresanunclassified
“…The usefulness of anti-Dsg1/3 ELISAs and indirect immunofluorescence (IIF) for the monitoring of pemphigus, based on a possible correlation between autoantibody levels and disease activity, remains controversial (3,4). A recent study showed that ELISA index values can be a valuable tool for monitoring the disease, whereas IIF titres insufficiently reflect clinical activity (5). However, an interesting report was published recently in which a patient with pemphigus vulgaris in remission had a high anti-Dsg3 antibody ELISA index, but negative IIF results (6).…”
Section: Sirmentioning
confidence: 99%
“…It is occasionally found that the results of Dsg ELISAs and indirect immunofluorescence (IF) do not correlate with disease activity (5). In addition, individuals with no clinical features of pemphigus may show positive results in Dsg ELISA (2).…”
Section: Yoshinao Muro Kazumitsu Sugiura and Masashi Akiyamamentioning
confidence: 99%